Effect of different drying methods on phenolic compounds and antioxidant activity of some Syrian eggplant varieties (Damascus University Journal of agriculture sciences, 2021)
A Study of three drying methods (solar drier, sun and traditional electrical oven) on phenolic compounds, antioxidant activity and rehydration properties of four Syrian eggplant verities :SHami ,Hamwy ,Homsy  and Agami: was investigated. Results showed that phenolic content ranged between 631.58 and 763.38 mg/100g dry weight .Drying  caused a significant reduction of phenolic content  and there was an effect  for either cultivar and drying method(p< 0.05)  .Phenolic content  in dried samples ranged between (60.56 and  657 mg dry basis  /100 g) .Solar drying has an effect in keeping phenolic content  compared with sun and oven methods . Antioxidant activity percent by DPPH method  ranged between 88.70 and 89.72% for fresh samples ,results showed that drying method and cultivar has no effect on antioxidant activity percent (p> 0.05) . Finally rehydration percent increased as boiling time has increased in different samples .Also rehydration percent has been affected by verities and method of drying, which recorded   7.22 and 7.00 in SHami and Hamwy respectively at time 45 minute.
Keywords: eggplant; drying methods; total phenolic; antioxidant activity